2020
DOI: 10.1002/cl2.1074
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: Effectiveness of interpersonal psychotherapy in comparison to other psychological and pharmacological interventions for reducing depressive symptoms in women diagnosed with postpartum depression in low and middle‐income countries: A systematic review

Abstract: Postpartum Depression (PPD) is highly prevalent among women in low and middle income countries (LMICs). World Heath Organization has recognised interpersonal Psychotherapy (IPT) as the first line treatment for the postpartum depression. The primary aim of this review is to evaluate the effectiveness of IPT alone or in combination with pharmacotherapy or other psychosocial therapies for treating depressive symptoms in women with postpartum depression. The generated evidence from this review will help to inform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The review is based on the protocol published (Kang, 2020 ). Randomized controlled trials (RCTs), feasibility trials, and quasi‐experimental designs were eligible for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The review is based on the protocol published (Kang, 2020 ). Randomized controlled trials (RCTs), feasibility trials, and quasi‐experimental designs were eligible for this study.…”
Section: Methodsmentioning
confidence: 99%
“…The standard treatment for postpartum depression typically includes psychotherapy and antidepressants. However, due to potential risks associated with exposing infants to antidepressants, psychotherapy is often the preferred treatment option for new mothers ( 27 ). Interpersonal psychotherapy is particularly relevant for postpartum depression as it focuses on the unique interpersonal challenges faced by women during the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Interpersonal psychotherapy is particularly relevant for postpartum depression as it focuses on the unique interpersonal challenges faced by women during the postpartum period. Interpersonal psychotherapy operates on the understanding that interpersonal issues arising during pregnancy, coupled with hormonal changes, can lead to depressive symptoms ( 27 ). Treatment approaches administered by mental health professionals can positively impact mothers with postpartum depression, leading to improved therapeutic outcomes and psychosocial enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that 50% of postpartum women experience depressive symptoms known as postpartum blues, with the rate of depressive symptoms continuing to increase to postpartum depression and usually cannot be cured without clinical intervention (1). In addition, postpartum blues is almost 80 percent experienced by mothers who give birth for the first time (2).…”
Section: Introductionmentioning
confidence: 99%